A global heterothermic continuum in mammals. Issue 9 (4th June 2013) - Boyles, Justin G.; Thompson, Amy B.; McKechnie, Andrew E.; Malan, Ezit; Humphries, Murray M.; Careau, Vincent
Abstract Aim The ability of endotherms to physiologically regulate body temperature (Tb) is presumed to be important in the adaptive radiation of birds and mammals. Recently, attention has shifted towards determining the extent and energetic significance of Tb variation documented in an ever‐expanding list of species. Thus, we provide the first global synthesis of ecological and evolutionary correlates of variation in mammalian Tb. Location World‐wide Methods We conducted a phylogenetically informed analysis of Tb variation using two complementary metrics, namely Thermoregulatory Scope (TS) and Heterothermy Index (HI), that treat Tb variation as a continuous variable. We included morphological (e.g. body mass), ecological (e.g. food habits) and environmental (e.g. latitude) correlates in the analysis. Results Among 560 mammal species included in the TS analysis, Tb relates most strongly to body mass (included in all models), season (relative parameter weight: 0.95), absolute latitude (0.80) and hoarding behavior (0.72), with small‐bodied, high latitude and non‐hoarding species expressing the most Tb variation. Small‐bodied and high latitude species also express a greater range of thermoregulatory patterns than large‐bodied and low latitude species. Results were generally similar in HI analysis, but in summer the extent of heterothermy decreases with latitude. Main conclusions Mammalian heterothermy is related to evolutionary history, climate conditions constraining minimum Tb, resource conditions mediating energy supply for maintaining high Tb, and latitudinal variation in the nature of seasonality. Our analysis further shows that traditional classification of mammals as hibernators, daily heterotherms or homeotherms is clouded or possibly misleading.